Antagonism of endogenous nociceptin/orphanin FQ inhibits infarction‐associated ventricular arrhythmias via PKC‐dependent mechanism in rats. (17th September 2013) - Han, Y; Guo, Z; Wang, L L; Zhang, L Z; Yao, T P
Abstract : Background and Purpose: Evidence indicates nociceptin/orphanin FQ (N/OFQ) may participate in the pathology of cardiac arrhythmias associated with myocardial infarction. But the role of N/OFQ in the arrhythmogenesis in acute myocardial infarction is unclear. The aim of this study was to investigate the effects of endogenous N/OFQ on infarction‐associated arrhythmias. Experimental Approach: The expression of N/OFQ, PKC activity and ventricular arrhythmias in presence and absence of UFP‐101, a specific antagonist of N/OFQ receptor, were examined following permanent coronary artery occlusion in anaesthetized rats. The effect of N/OFQ on action potential duration was examined in isolated rat cardiomyocytes. Key Results: It was observed that N/OFQ was increased by 41% in the myocardium after coronary artery occlusion ( P < 0.01 vs. control). Pretreatment with UFP‐101 (10 −7  mol·kg −1, i.v.) reduced the incidence of ventricular ectopic beats by 70% and ventricular tachycardia by 51% respectively (all P < 0.05 vs. control). Meanwhile, PKC activity was elevated in the rats treated with UFP‐101 (by 35%, P < 0.05 vs. control). A selective PKC inhibitor, calphostin C, completely abolished the anti‐arrhythmic effects of UFP‐101 ( P < 0.01). N/OFQ (at 10 −11, 10 −9 and 1 × 10 −7  mol·L −1 ) shortened the action potential duration by 3% ( P > 0.05), 10% ( P < 0.05) and 22% ( P < 0.01), respectively, via N/OFQ receptor. Conclusions and Implications: Antagonism of endogenous N/OFQ produces anti‐arrhythmic effects on ventricular arrhythmias in acute myocardial infarction, possibly via modulating PKC activity and action potential of myocytes.